Board gender diversity and cash holdings: Empirical evidence from the European sport and leisure sector - Panagiotis Dimitropoulos; Konstantinos Koronios (International Journal of Financial Studies, 2021)
The scope of this study is to examine the impact of board gender diversity on corporate cash-holding decisions within the European sport and leisure sector. A sample of 125 unique firms was selected for the period from 2008 to 2019, and analysis was performed using panel fixed-effects regressions. Empirical evidence documented that the higher the number of women serving on the board of directors, the higher the level of cash the firm holds. This result is attributed to the critical mass theory of governance, suggesting that boards having at least two women directors are associated with higher cash holdings compared to firms with one or no women directors. Additionally, gender diversity leads to increased cash holdings for firms with lower governance quality, suggesting that women on boards perform a monitoring role within those firms with the most severe agency problems. The results remain robust after several sensitivity tests controlling for potential endogeneity among the variables and the model's functional form.
Keywords: 330; board gender diversity; cash-holding decisions; corporate governance quality; critical mass theory; Europe; sport and leisure sector